Biennial Review of Planar Chromatography: 2013–2015. (27th November 2019) - Sherma, Joseph
Abstract: The most important advances in planar chromatography published between November 1, 2013 and November 1, 2015 are reviewed in this paper. Included are an introduction to the current status of the field; student experiments, books, and reviews; apparatus and techniques for sample preparation and TLC separations; detection and identification of separated zones; quantitative analysis; preparative layer chromatography; and thin layer radiochromatography. Selected applications are given in the various sections of the review.